Validation and Analysis of GEMS Aerosol Optical Depth Product Against AERONET over Mainland Southeast Asia - Beomgeun Jang; Dimitris Stratoulias; Aekkapol Aekakkararungroj; Peeranan Towashiraporn (Aerosol and Air Quality Research)
Abstract Purpose Agricultural biomass burning is a major source of seasonal PM2.5 emissions in Southeast Asia. Monitoring this pollution remains challenging due to its large spatial extent and the fragmented, small-scale nature of emission sources. This study evaluates the usability of aerosol products from the Geostationary Environment Monitoring Spectrometer (GEMS) by cross-validating them with AERONET ground-based observations in mainland Southeast Asia. Methods Aerosol Optical Depth (AOD) and related parameters from GEMS were compared with data from 12 AERONET stations across Thailand, Lao PDR, and Cambodia from 2021 to 2024. Correlation analyses were conducted on seasonal and hourly intra-day scales, with further evaluations of Single Scattering Albedo (SSA), Ångström Exponent (AE), and Aerosol Layer Height (ALH) to assess aerosol properties. Results A distinct peak in AOD peak was observed each April. Correlations between GEMS and AERONET AOD were higher during the dry seasons (R2 = 0.63–0.79), but dropped during the rainy season (R2 = 0.11–0.13). Overall, the datasets showed good agreement (R2 = 0.75), though GEMS tending to underestimate the AOD. Intra-day comparisons showed improved correlations (R2 = 0.76–0.84) with regression slope gradually increased from 0.29 to 0.85. Seasonal analysis of SSA and AE indicated the dominance of optically absorbing, fine-mode aerosols from biomass burning during high AOD periods. ALH data showed that elevated AOD layers at altitude of 2–3 km during the dry season. Conclusion GEMS demonstrated strong association with AERONET data in mainland Southeast Asia, especially during the dry seasons, and is a promising tool for monitoring aerosol pollution and supporting regional air quality assessments in Southeast Asia. Graphical Abstract